Flower Development and Sex Determination between Male and Female Flowers in Vernicia fordii - Mao, Yingji; Liu, Wenbo; Chen, Xue; Xu, Yang; Lu, Weili; Hou, Jinyan; Ni, Jun; Wang, Yuting; Wu, Lifang (Frontiers in Plant Science, 2017)
Vernicia fordii is a monoecious and diclinous species with male and female flowers on the same inflorescence. Low female to male flower ratio is one of the main reasons for low yield in this species. However, little is known of its floral development and sex determination. Here, according to the results of scanning electron microscopy and histological analysis, the floral development of V. fordii was divided into 12 stages and the first morphological divergence between the male and female flowers was found to occur at stage 7. The male flowers are always unisexual, but the female flowers present bisexual characteristics, with sterile stamen (staminode) restricted to pre-meiosis of mother sporogenous cells and cell death occurring at later development stages. To further elucidate the molecular mechanism underling sex determination at the divergence stage for male and female flowers, comparative transcriptome analysis was performed. In total, 56,065 unigenes were generated and 608 genes were differentially expressed between male and female flowers, among which 310 and 298 DEGs (differentially expressed genes) showed high expression levels in males and females, respectively. The transcriptome data showed that the sexual dimorphism of female flowers was affected by jasmonic acid, transcription factors and some genes related to the floral meristem activity. 10 candidate genes showed consistent expression in the qRT-PCR validation and DEGs data. In this study, we provide developmental characterization and transcriptomic information for better understanding of the development of unisexual flowers and the regulatory networks underlying the mechanism of sex determination in V. fordii, which would be helpful in the molecular breeding of V. fordii to improve the yield output.